A Urine-based DNA Methylation Marker Test to Detect Upper Tract Urothelial Carcinoma: A Prospective Cohort Study. Issue 5 (16th May 2023) - Ghoreifi, Alireza; Ladi-Seyedian, Seyedeh-Sanam; Piatti, Paolo; Chew, Yap Ching; Jara, Benjamin; Sanossian, Lucy; Bhasin, Jeffrey M.; Yamada, Taikun; Fuchs, Gerhard; Bhanvadia, Sumeet; Sotelo, Rene; Hung, Andrew; et al.
Abstract : Purpose: We explored the accuracy of a urine-based epigenetic test for detecting upper tract urothelial carcinoma. Materials and Methods: Under an Institutional Review Board–approved protocol, urine samples were prospectively collected from primary upper tract urothelial carcinoma patients before radical nephroureterectomy, ureterectomy, or ureteroscopy between December 2019 and March 2022. Samples were analyzed with Bladder CARE, a urine-based test that measures the methylation levels of 3 cancer biomarkers (TRNA-Cys, SIM2, and NKX1-1) and 2 internal control loci using methylation-sensitive restriction enzymes coupled with quantitative polymerase chain reaction. Results were reported as the Bladder CARE Index score and quantitatively categorized as positive (>5), high risk (2.5-5), or negative (<2.5). The findings were compared with those of 1:1 sex/age-matched cancer-free healthy individuals. Results: Fifty patients (40 radical nephroureterectomy, 7 ureterectomy, and 3 ureteroscopy) with a median (IQR) age of 72 (64-79) years were included. Bladder CARE Index results were positive in 47, high risk in 1, and negative in 2 patients. A significant correlation was found between Bladder CARE Index values and tumor size. Urine cytology was available for 35 patients, of whom 22 (63%) results were false-negative. Upper tract urothelial carcinoma patients had significantly higher Bladder CARE Index values compared to the controls (mean 189.3 vs 1.6, P < .001). The sensitivity, specificity, positive predictive value, and negative predictive value of the Bladder CARE test for detecting upper tract urothelial carcinoma were 96%, 88%, 89%, and 96%, respectively. Conclusions: Bladder CARE is an accurate urine-based epigenetic test for the diagnosis of upper tract urothelial carcinoma, with much higher sensitivity than standard urine cytology.